1997
DOI: 10.1190/1.1444123
|View full text |Cite
|
Sign up to set email alerts
|

The subsurface structure of the Chalco sub‐basin (Mexico City) inferred from geophysical data

Abstract: The Chalco sub‐basin, the hydrogeological reserve of Mexico City, is located in the southern portion of Mexico City's basin, an intramontane valley located at 2200 m a.s.l. in the Trans‐Mexican Volcanic Belt (Central Mexico). Several geophysical studies (dc resistivity, seismic refraction, gravity, well‐logging) have been conducted in this area. The objectives of these independent surveys were different and of regional and local scopes. This study represents the first comprehensive effort to assimilate and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…6. The Xicomulco Fault (number 16 in Figure 2; García-Palomo et al, 2008) correlates quite well with the faults delimiting graben and half-graben type structures in the Chalco sub-basin (number 17 in Figure 2; Campos-Enríquez et al, 1997). It is featured by seismic activity around Milpa Alta (Rodríguez et al, 1984;UNAM and CENAPRED Seismology Group, 1995, this study).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…6. The Xicomulco Fault (number 16 in Figure 2; García-Palomo et al, 2008) correlates quite well with the faults delimiting graben and half-graben type structures in the Chalco sub-basin (number 17 in Figure 2; Campos-Enríquez et al, 1997). It is featured by seismic activity around Milpa Alta (Rodríguez et al, 1984;UNAM and CENAPRED Seismology Group, 1995, this study).…”
Section: Discussionmentioning
confidence: 84%
“…8. At a local scale, Campos-Enríquez et al (1997) established the existence of shallow E-W trending faults conforming graben and half-graben type structures in the Chalco sub-basin (17), where previously Vázquez-Sánchez and Jaimes-Palomera (1989) proposed the existence of a graben. Different stress regimes are observed to the north and south of the Trans-Mexican Volcanic Belt.…”
Section: Geological Settingmentioning
confidence: 99%
“…CDMX is divided into three geotechnical zones (I: hill; II: transition; III: lake) depending on the site conditions and location with respect to the lake basin, as per the 2017 local code (Órgano de Difusión del Gobierno de la Ciudad de México (ODG-CDMX), 2017). The soft clays are typically found within Zones II and III, and are known to be interlayered with thin silt and sand layers, with a unique mineralogical structure when compared with more conventional soils, trapping large volumes of water in an open, flocculated structure (Auvinet and Juárez, 2003; Auvinet and Moises, 2011; Campos-Enríquez et al, 1997; Díaz-Rodríguez, 1989; Díaz-Rodríguez et al, 1992, 1998; Fernández, 1994; Mesri et al, 1975; Nikolaou et al, 2019; Ovando-Shelley, 2007; Ovando-Shelley, 2011; Romo et al, 1988). The extraordinary mechanical and physical properties of CDMX’s soils are expressed in excessively high natural water contents and plasticity indices that make them very compressible, causing alarming continuous settlements throughout the city (Arroyo et al, 2013; Avilés and Pérez-Rocha, 2010; Martínez-González et al, 2012), as observed in the Palacio de Bellas Artes of CDMX, where recorded settlements have exceeded 7 m between early 1900s and 1980s (Lambe and Whitman, 1969; Santoyo, 2012), and keeps increasing to date at an average rate of 300 mm/year (Sowter et al, 2016).…”
Section: Geotechnical Characterizationmentioning
confidence: 99%
“…En este graben ha sido reconocido un alto estructural de orientación NE-SW, que coincide con el alineamiento de los volcanes Xico y Tlapacoya, y que dividen al graben en dos cuencas E y W (Urrutia-Fucugauchi y Chávez-Segura, 1991;Campos Enríquez et al, 1997).…”
Section: Ubicación Y Características Geológicasunclassified